Screening for resistance to four fungal diseases and associated genomic regions in a snap bean diversity panel - Campa, Ana; Geffroy, Valérie; Bitocchi, Elena; Noly, Alicia; Papa, Roberto; Ferreira, Juan José (Frontiers in Plant Science, 2024)
Anthracnose, white mold, powdery mildew, and root rot caused by Colletotrichum lindemuthianum, Scletorinia sclerotiorum, Erysiphe spp., and Pythium ultimum, respectively, are among the most frequent diseases that cause significant production losses worldwide in common bean (Phaseolus vulgaris L.). Reactions against these four fungal diseases were investigated under controlled conditions using a diversity panel of 311 bean lines for snap consumption (Snap bean Panel). The genomic regions involved in these resistance responses were identified based on a genome-wide association study conducted with 16,242 SNP markers. The highest number of resistant lines was observed against the three C. lindemuthianum isolates evaluated: 156 lines were resistant to CL124 isolate, 146 lines resistant to CL18, and 109 lines were resistant to C531 isolate. Two well-known anthracnose resistance clusters were identified, the Co-2 on chromosome Pv11 for isolates CL124 and CL18, and the Co-3 on chromosome Pv04 for isolates CL124 and C531. In addition, other lesser-known regions of anthracnose resistance were identified on chromosomes Pv02, Pv06, Pv08, and Pv10. For the white mold isolate tested, 24 resistant lines were identified and the resistance was localized to three different positions on chromosome Pv08. For the powdery mildew local isolate, only 12 resistant lines were identified, and along with the two previous resistance genes on chromosomes Pv04 and Pv11, a new region on chromosome Pv06 was also identified. For root rot caused by Pythium, 31 resistant lines were identified and two main regions were located on chromosomes Pv04 and Pv05. Relevant information for snap bean breeding programs was provided in this work. A total of 20 lines showed resistant or intermediate responses against four or five isolates, which can be suitable for sustainable farm production and could be used as resistance donors. Potential genes and genomic regions to be considered for targeted improvement were provided, including new or less characterized regions that should be validated in future works. Powdery mildew disease was identified as a potential risk for snap bean production and should be considered a main goal in breeding programs.